Incidence of complicated acute appendicitis: a single-centre retrospective study - Piotrowska, Aneta; Osman, Sławomir; Wolak, Przemysław K. (Medical Studies/Studia Medyczne, 2017)
Introduction : Abdominal pain has been one of the most common reasons patients seek medical care for centuries. Nowadays, together with laboratory diagnostics and imaging, we are able to make an early diagnosis. This leads to the introduction of early adequate treatment. Aim of the research : To analyse the incidence and causes of complicated acute appendicitis in one medical centre in between 2004 and 2016. Material and methods : A retrospective study covered the period from December 23, 2004 to November 07, 2016. It included 2048 cases of children between 0 and 18 years of age undergoing surgery for suspected acute appendicitis.  Demographic and clinical characteristics as well as length of hospitalisation, antibiotics schemes, and intraoperative diagnosis were reviewed. Complicated acute appendicitis cases were distinguished and compared with the incidence in world literature. Results : The percentage of complicated acute appendicitis ranged from 39% to 60%. Complicated acute appendicitis occurs much more often in children under 5 years of age. Conclusions : The delay and failure in diagnosis of acute appendicitis results in higher incidence of complicated acute appendicitis; consequently, there are higher costs of treatment. Improving the awareness of parents and primary care physicians may allow faster diagnosis and treatment of acute appendicitis. It was noted that the reform of the National Emergency Medical Services in Poland contributed to a reduction in the incidence of complicated appendicitis.